Fruit and Restaurant Waste Polysaccharides Recycling Producing Xylooligosaccharides - Pereira, Beatriz Salustiano [UNESP]; Schmatz, Alison Andrei [UNESP]; de Freitas, Caroline [UNESP]; Masarin, Fernando [UNESP]; Brienzo, Michel [UNESP] (MDPI, 2023)
A significant part of fruit production is wasted annually, a material of high value without use, causing environmental and social damage. These residues from agro-industrial processes, or those that can no longer be used in the market, can be recycled and generate value-added products by pretreatments/hydrolysis. One of the important pretreatments is acid hydrolysis, which can produce xylooligosaccharides (XOS) from biomass, a product of great commercial value in the food and pharmaceutical markets, mainly due to its prebiotic potential. Bananas, oranges, and guava generate a large volume of waste and represent much of Brazil’s fruit production. The dilute acid hydrolysis resulted in XOS production of 37.69% for banana peel, 59.60% for guava bagasse, 28.70% for orange bagasse, and 49.64% for restaurant residue. XOS were quantified by a liquid chromatograph system with a Bio-Rad Aminex HPX-87C column. The results show that, for this type of material and hydrolysis, the ideal conditions to produce XOS are high temperature, low time, and high acid concentration for banana peel residue (160 °C, 15 min, and 3% H2SO4), low temperature, low time, and high acid concentration for guava bagasse (100 °C,15 min and 3% H2SO4), high temperature and acid concentration with low time for orange bagasse (160 °C,15 min and 3% H2SO4) and high temperature and time and high acid concentration for restaurant waste (160 °C, 55 min and 3% H2SO4). This study identified acid hydrolysis conditions that maximized XOS production with a low amount of xylose production using agro-industrial and food residues, also showing the high potential of the chosen residues through the high yields of XOS production.
Keywords: acid hydrolysis; agro-industrial waste; biomass; prebiotic; xylooligosaccharides